Interleukin-4 Receptor α Subunit Deficiency Alleviates Murine Intestinal Inflammation In Vivo Through the Enhancement of Intestinal Mucosal Barrier Function - Hertati, Ai; Hayashi, Shusaku; Ogawa, Yudai; Yamamoto, Takeshi; Kadowaki, Makoto (Frontiers in Pharmacology, 2020)
Disturbance of epithelial barrier function causes chronic intestinal inflammation such as inflammatory bowel disease. Several studies have reported that Th2 cytokines such as interleukin (IL)-4 and IL-13 play an important role in the regulation of intestinal barrier function. However, the precise role of the IL-4 receptor α subunit (IL-4Rα) in intestinal inflammation remains unclear. Thus, we used an experimental colitis model to investigate the role of IL-4Rα in intestinal inflammation. IL-4Rα-deficient (IL-4Rα-/-) mice and their littermate wild-type (WT) mice were used. Experimental colitis was induced by administration of 3% dextran sulfate sodium (DSS) in the drinking water for 7 days. Treatment with DSS caused body weight loss, an increase in the disease activity index and histological abnormalities in WT colitis mice, all of which were significantly attenuated in IL-4Rα-/- colitis mice. Neutrophil infiltration in the colonic mucosa was reduced in IL-4Rα-/- colitis mice compared with WT colitis mice. NADPH oxidase 1 (NOX1) expression and reactive oxygen species (ROS) production were increased in the colons of IL-4Rα-/- mice. Furthermore, elevated intestinal permeability induced by DSS treatment was suppressed in IL-4Rα-/- colitis mice. These results demonstrate that IL-4Rα-/- mice exhibit reduced susceptibility to DSS-induced colitis. Our present findings suggest that IL-4Rα deficiency enhances intestinal mucosal barrier function through the upregulation of NOX1-dependent ROS production, thereby suppressing the development of intestinal inflammation.